2022
DOI: 10.1177/10497323221092350
|View full text |Cite
|
Sign up to set email alerts
|

Development of PARcific Approach: Participatory Action Research Methodology for Collectivist Health Research

Abstract: This article explores the evolution of a novel approach designed to advance qualitative methods in cross-cultural health research. This methodology was developed by synthesising several research methods and involved in-depth stakeholder consultation with participants of a Pacific-based nursing and midwifery health leadership program. Many of these participants played a crucial role in creating, exploring and evaluating several research methods and implementing and evaluating this co-designed research methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 47 publications
(80 reference statements)
0
18
0
Order By: Relevance
“…The goal of both is to create a framework that is trusted by communities and will lead to a truly collaborative approach that is owned by the partners who engage with the program. The grounds-up and partnership approach was developed in collaboration with SPCNMOA (Rumsey et al, 2022) and illustrated in this paper is a potential approach to assist meeting global and regional health outcomes. The goal is to use a framework and methodology that is trusted by Pacific communities and will lead to a truly collaborative approach that is owned by the partners who engage with the program.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The goal of both is to create a framework that is trusted by communities and will lead to a truly collaborative approach that is owned by the partners who engage with the program. The grounds-up and partnership approach was developed in collaboration with SPCNMOA (Rumsey et al, 2022) and illustrated in this paper is a potential approach to assist meeting global and regional health outcomes. The goal is to use a framework and methodology that is trusted by Pacific communities and will lead to a truly collaborative approach that is owned by the partners who engage with the program.…”
Section: Discussionmentioning
confidence: 99%
“…Rumsey et al (2022) found that having a GCNMO to advise the Minister of Health was crucial to having a nursing and midwifery voice in policy decisions. But the development of a confident representative who is able to articulate policy positions requires appropriate, tailored leadership programs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations